Work Procrastination in Young Police Officers: An Analysis Based on Self-Efficacy Levels - Yugo Wicaksono, Alif; Handayani Harahap, Dewi; Gigih Rizqia, Ayu (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
This research is motivated by the high public scrutiny of the Indonesian National Police (Polri) performance, reflected in the crisis of public trust and indications of work procrastination in field units. This study aims to analyze the relationship between self-efficacy and work procrastination among personnel of the Samapta Directorate (Ditsamapta) of the DIY Regional Police. A quantitative correlational method was employed with a sample of 116 respondents, predominantly from the Dalmas Sub-directorate (74.1%) and within the emerging adulthood age range (19-21 years). Data were collected using self-efficacy and work procrastination scales, then analyzed using Pearson Product Moment correlation. The hypothesis test results indicate a significant negative relationship between self-efficacy and work procrastination (r = -0.449**, p <0.05), with self-efficacy contributing -44.9% to the reduction of task-delaying behavior. Categorization results show that the majority of personnel possess moderate levels of both self-efficacy and work procrastination. Partially, generality and strength aspects emerged as the strongest predictors in minimizing delays in starting tasks. The implications of this study emphasize that strengthening mentality through increased self-confidence is a crucial instrument in suppressing work procrastination.Penelitian ini dilatarbelakangi oleh tingginya sorotan publik terhadap kinerja Polri, yang tercermin melalui fenomena krisis kepercayaan masyarakat dan indikasi prokrastinasi kerja di unit-unit lapangan. Fokus penelitian ini adalah untuk menganalisis hubungan antara efikasi diri dengan prokrastinasi kerja pada personel Direktorat Samapta (Ditsamapta) Polda DIY. Metode penelitian yang digunakan adalah kuantitatif korelasional dengan sampel sebanyak 116 responden, yang mayoritas berasal dari Subdit Dalmas (74,1%) dan berada pada rentang usia dewasa awal (19-21 tahun). Data dikumpulkan menggunakan skala efikasi diri dan skala prokrastinasi kerja, kemudian dianalisis menggunakan uji korelasi Pearson Product Moment. Hasil uji hipotesis menunjukkan adanya hubungan negatif yang signifikan antara efikasi diri dan prokrastinasi kerja (r = -0.449**, p <0.05), di mana efikasi diri memberikan kontribusi efektif sebesar -44,9% terhadap penurunan perilaku menunda pekerjaan. Hasil kategorisasi menunjukkan bahwa mayoritas personel berada pada tingkat efikasi diri dan prokrastinasi kerja yang moderat. Secara parsial, aspek generality dan strength menjadi prediktor terkuat dalam meminimalisir keterlambatan memulai tugas. Implikasi penelitian ini menegaskan bahwa penguatan mentalitas melalui peningkatan keyakinan diri merupakan instrumen krusial dalam menekan prokrastinasi kerja.